Seleccion para resistencia a insectos. Manejo de la plaga y metodologia de evaluacion y seleccion - Cardona, C. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Obtaining insect-resistant var. involves (1) searching for sources of resistance, (2) reconfirming levels of resistance, (3) hybriding, and (4) selecting resistant progenies. Sources of resistance can be obtained from native var., introduced foreign var., wild (uncultivated) materials, and materials of other species of the same genera. In beans, this search is done through mass screening of germplasm, in which reconfirmation of resistance is extremely important, since the method allows uniform distribution of the pests within the field and the var. evaluated are necessarily attacked by the insect. (CIAT)